The State You See How Government Visibility Creates Political Distrust and Racial Inequality - Rosenthal, Aaron J. (University of Michigan Press, 2023)
The State You See uncovers a racial gap in the way the American government appears in people's lives. It makes it clear that public policy changes over the last fifty years have driven all Americans to distrust the government that they see in their lives, even though Americans of different races are not seeing the same kind of government. For white people, these policy changes have involved a rising number of generous benefits submerged within America's tax code, which taken together cost the government more than Social Security and Medicare combined. Political attention focused on this has helped make welfare and taxes more visible representations of government for white Americans. As a result, white people are left with the misperception that government does nothing for them, apart from take their tax money to spend on welfare. Distrust of government is the result. For people of color, distrust is also rampant but for different reasons. Over the last fifty years, America has witnessed increasingly overbearing policing and swelling incarceration numbers. These changes have disproportionately impacted communities of color, helping to make the criminal legal system a unique visible manifestation of government in these communities. While distrust of government emerges in both cases, these different roots lead to different consequences. White people are mobilized into politics by their distrust, feeling that they must speak up in order to reclaim their misspent tax dollars. In contrast, people of color are pushed away from government due to a belief that engaging in American elections will yield the same kind of unresponsiveness and violence that comes from interactions with the police. The result is a perpetuation of the same kind of racial inequality that has always been present in American democracy. The State You See is essential reading for anyone interested in understanding how the American government engages in subtle forms of discrimination and how it continues to uphold racial inequality in the present day.